Jump dominance on the contaminant transport residual error estimator - Martins,J.P. (2014)
Considering the fact that the transport of contaminants occur in small advection regime, a residual estimator is used to evaluate the parabolic equation that describes the phenomena of advection-diffusion-reaction in the saturated porous medium. The correspondent numerical solution is obtained by the finite element method using the θ A-stable scheme and a Python code. The residual error estimator considers its component parts and enables analysis and comparisons of contributions to residual error.This analysis considers a problem sequence with a different number of elements in computational mesh. As a result of numerical simulations, there is a dominance of the jump residuals compared to other residual estimates and this dominance increases with both, the growth of elements number in the computational mesh and with time. Furthermore, the considered problem requires additional effort for the calculation of contributions associated with the L² projection of the contaminant source function on the finiteelement space.